STRATEGIES OF MAINTAINING PROFICIENCY BY TEACHERS OF ENGLISH IN INDONESIA - Alfan Zuhairini, Junaidi Mistar, (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
The objectives of the present study are four-fold: (1) to identify the types of strategies to maintain proficiency used by teachers of English in Indonesia, (2) to know the intensity of use of the obtained strategy types, (3) to measure the inter-correlation in the use of the obtained strategy types, and (4) to investigate the effect of proficiency level on the use of maintaining strategies. The subjects were 93 teachers applying for S2 degree in 2010/2011 at the postgraduate program of the Islamic University of Malang. They were given two sets of instrument, a Likert-scale questionnaire of English proficiency maintaining strategies and a TOEFL test. Then, a factor analysis identified nine strategy categories, including language focusing, metacognitive and affective developing, reading and writing activating, language resource utilizing, cognitive processing, culture learning, social communicating, text analyzing, and radio listening strategies. These strategy types explained 63.84% of variances of maintaining strategies and they were used at high level of intensity. Moreover, the use of the nine strategy types were found to be inter-correlated with one another. Finally, no significant effect of proficiency level on strategy use was found, indicating that teachers with different level of proficiency reported using the same strategies of maintaining their proficiency.